Pengurangan Sampah Rumah Tangga : Alternatif Bank Sampah - Anggina Khairani Harahap; Nurganti Nurganti; Rahma Aulia Hasanah; M. Ikhsani Simanjorang; Sari Wulandari (Lembaga Pengembangan Kinerja Dosen, 2025)
Managing household waste effectively is one of the biggest problems facing modern society. Waste division and sorting is one option. As one option to minimize the amount of household waste, Bank Sampah Sahabat Mitra/Pupuk Kompos in Bandar Kalipah, North Sumatra is a waste bank. This waste bank minimizes the amount of waste disposed of in landfills by implementing a systematic system to collect, group, and process waste. In addition, by carrying out composting operations, this waste bank contributes to the economical use of organic waste. Investigating The purpose of this study was to determine to what extent waste banks can reduce the volume of household waste and increase public awareness of the importance of sustainable waste management. The results showed that the success of the waste bank program is highly dependent on active community participation and support from local governments. As a result, waste banks can be a model for sustainable and effective waste management that can be emulated by other cities.